2022
DOI: 10.1002/hsr2.920
|View full text |Cite
|
Sign up to set email alerts
|

The impact of violence on healthcare workers' mental health in conflict based settings amidst COVID‐19 pandemic, and potential interventions: A narrative review

Abstract: Healthcare workers (HCWs) have faced an increased amount of mental health struggles amidst the COVID-19 pandemic. However, those in conflict-based settings with fragile healthcare systems meet additional challenges. This study reviews violence, conflict and mental health among HCWs in five countries: Syria, Palestine, Yemen, Afghanistan and Lebanon. Our study reports that HCWs are targeted by violence, bombings, mistreatment and different forms of abuse, including verbal and physical. With the additional burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This could be attributed to the impact of violence, which manifests as decreased productivity and concentration, impaired quality of work, higher use of defensive medicine and psychological consequences (over-stress, depression or Post Traumatic Stress Disorder (PTSD)), ultimately affecting the quality of patient care 48 50–52. Recently, several recommendations have been proposed to curb violence against HCWs to protect and enhance their mental health 53…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to the impact of violence, which manifests as decreased productivity and concentration, impaired quality of work, higher use of defensive medicine and psychological consequences (over-stress, depression or Post Traumatic Stress Disorder (PTSD)), ultimately affecting the quality of patient care 48 50–52. Recently, several recommendations have been proposed to curb violence against HCWs to protect and enhance their mental health 53…”
Section: Discussionmentioning
confidence: 99%
“… 48 50–52 Recently, several recommendations have been proposed to curb violence against HCWs to protect and enhance their mental health. 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review highlights relevant studies to violence on Health care workers from 2003 to 2021 in ve countries with armed con ict. The study showed that violence has a strong association with the rapidly deteriorating mental health of the health care workers in con ict-based setting across the World (23).…”
Section: Medical Professionals In Haiti Are At High Risk Of Kidnappingmentioning
confidence: 95%